The Morphology of Pangururan District (International Journal of Architecture and Urbanism, 2022)
This study discusses the morphology of the Pangururan District in terms of its forming factors, spatial expressions formed, solid-void patterns, and building typology. It is necessary because, as the capital of Samosir Regency, Pangururan District often experiences growth and development. So, it is essential to understand the morphology of this district to avoid collisions between the problem of physical form and the quality demands of urban planning. Using a qualitative descriptive research methodology approach, researchers collect the data needed by secondary data collection techniques, namely through related literature studies. The results showed that Pangururan District had fan-shaped cities and fragmented cities. Moreover, the configuration of the solid-void space forms an organic pattern. The typology of community settlements scattered alongside the waterfront adapts to the physical form of nature and nearby tradition.